PENGARUH UKURAN KAP, FINANCIAL DISTRESS, AUDIT FEE, PERGANTIAN MANAJAMEN, DAN BACKGROUND KOMITE AUDIT TERHADAP AUDITOR SWITCHING - Fauziah, Nadila; Zakaria, Adam; Gurendrawati, Etty (LPPM Universitas Bina Bangsa, 2023)
This study aims to examine whether there is an effect of KAP size, financial distress, audit fees, management changes, and audit committee background on auditor switching. The population in this study are companies in the infrastructure, utilities and transportation sectors. The number of samples in this study were 41 companies. The sampling technique used purposive sampling method. The research method used is quantitative with data sources in the form of secondary data. Methods of data analysis using logistic regression analysis with SPSS version 20. The results of this study provide empirical evidence that partially the independent variable financial distress has a positive effect on auditor switching. Meanwhile, the variables of KAP size, audit fees, management turnover, and audit committee background have no effect on auditor switching. Simultaneously the independent variables of KAP size, financial distress, audit fees, management changes, and audit committee background have no effect on auditor switching